2012
DOI: 10.1111/j.1365-2966.2012.21471.x
|View full text |Cite
|
Sign up to set email alerts
|

Emission-line stars discovered in the UKST Hα survey of the Large Magellanic Cloud - I. Hot stars

Abstract: We present new, accurate positions, spectral classifications, radial and rotational velocities, Hα fluxes, equivalent widths and B, V, I, R magnitudes for 579 hot emission‐line stars (classes B0–F9) in the Large Magellanic Cloud (LMC) which include 469 new discoveries. Candidate emission‐line stars were discovered using a deep, high‐resolution Hα map of the central 25 degree2 of the LMC obtained by median stacking a dozen 2 h Hα exposures taken with the UK Schmidt Telescope (UKST). Spectroscopic follow‐up obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 96 publications
0
33
0
Order By: Relevance
“…The emission features are centered on the velocity of the cluster, +298.5 km s −1 (Mucciarelli et al 2011). The profiles are typical of those found in Be stars in which the emission arises in a Keplerian decretion disk surrounding a rapidly rotating star (Reid & Parker 2012;Rivinius et al 2013;Paul et al 2017). Differences in the profile shapes result from the angle of observation, from pole-on to equator (Struve 1931).…”
Section: Discussionmentioning
confidence: 70%
“…The emission features are centered on the velocity of the cluster, +298.5 km s −1 (Mucciarelli et al 2011). The profiles are typical of those found in Be stars in which the emission arises in a Keplerian decretion disk surrounding a rapidly rotating star (Reid & Parker 2012;Rivinius et al 2013;Paul et al 2017). Differences in the profile shapes result from the angle of observation, from pole-on to equator (Struve 1931).…”
Section: Discussionmentioning
confidence: 70%
“…This brings the total number of WRs in the LMC to 138 stars (134 stars from BAT99 + 6 newly discovered stars -2 demoted stars = 138 stars). Reid & Parker (2012) mention finding several additional WRs in the LMC using spectroscopic followup to an Hα imaging survey, but they plan to give details (coordinates, spectral types) in a future paper. W. Reid (2012, private communication) has confirmed that our newly found WO4 star is not among them.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the basis of this new detection is not clear. Another six new WR stars in the LMC are reported by Reid & Parker (2012), but without giving coordinates or closer classifications. We do not include any of these newly discovered WN stars in our analyses.…”
Section: Sample Selectionmentioning
confidence: 99%